Understanding public perceptions of wood-based electricity production in wisconsin, united states: the place-based dynamics of social representations - Banerjee, A., Schelly, C., Halvorsen, K. E. (My University, 2017)
Public support is critical to renewable energy sector growth, an important element of reducing fossil fuel dependence and mitigating climate change. Prevalent understandings of public support for renewable energy projects often work within a binary framework of acceptance and non-acceptance, arguably unable to capture the nuances of localized public responses to specific projects. Taking a place-based approach and insights from social representation theory, we report on public responses to wood-based electricity production in Wisconsin, USA. Findings indicate that public responses are tied to social and cultural contexts, varying in relation to community histories and identities shaped by other community resources. These results suggest that public perceptions of renewable energy technologies are shaped by representations formed in socio-spatial context, offering insight to inform future decisions in the renewable energy policy process.
Keywords: Public perceptions of technology, bioenergy, renewable energy, place-based approach, social representation theory, bioelectricity